Protease of Ficus bengalesis - Khan, M.R.; Amir, M. (Asian Journal of Chemistry, 2012)
The protease contents of the freeze-dried leaves of Ficus bengalesis was determined. The extraction of the protease was carried using buffers of different pH. The extraction was maximum with buffer pH 8.2. The extracted protease was characterized by studying on its activity by effect of temperature, pH and substrates such as casein, meat and minced meat. The research activity was further extended to study its thermostability and its pH-stability. The whole plant was found rich in protease activity. Its freeze-dried sample contained 17.6 units of activity/g. The activity of the protease of Ficus begalinensis was optimum at 40 ºC and afterward decreased with the increase of temperature. The pH-profile exhibited three pH optima.